2023
DOI: 10.1186/s12915-023-01693-0
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of deltamethrin resistance evolution in Aedes albopictus has an impact on fitness and dengue virus type-2 vectorial capacity

Yijia Guo,
Ke Hu,
Jingni Zhou
et al.

Abstract: Background Worldwide invasion and expansion of Aedes albopictus, an important vector of dengue, chikungunya, and Zika viruses, has become a serious concern in global public health. Chemical insecticides are the primary means currently available to control the mosquito populations. However, long-term and large-scale use of insecticides has selected for resistance in the mosquito that is accompanied by a genetic load that impacts fitness. Results A n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…In the last five decades, there has been an approximately 30-fold increase in the incidence of dengue fever worldwide, and a recent study suggested that different species of mosquitoes will continue to spread globally in the coming decades, with a significant increase in the incidence of dengue fever by 2050 [7, 8]. Chemical control using insecticides is an important means to control mosquito-borne diseases [9]. Pyrethroids are the only insecticides recommended by the World Health Organization for use in mosquito nets.…”
Section: Introductionmentioning
confidence: 99%
“…In the last five decades, there has been an approximately 30-fold increase in the incidence of dengue fever worldwide, and a recent study suggested that different species of mosquitoes will continue to spread globally in the coming decades, with a significant increase in the incidence of dengue fever by 2050 [7, 8]. Chemical control using insecticides is an important means to control mosquito-borne diseases [9]. Pyrethroids are the only insecticides recommended by the World Health Organization for use in mosquito nets.…”
Section: Introductionmentioning
confidence: 99%